HUBUNGAN PARTISIPASI DAN KETERLIBATAN MANAJER SERTA DIMENSI KUALITAS DENGAN PENGAMBILAN KEPUTUSAN DAN KEPUASAN PEMAKAI - Hidayat, Riskin (potensio, 2012)
The development of information technology is quickly influence to firm and public. Currently,managers as those who manage a firm is required to understand about information technology,participate and directly involved in the information technology systems used by the firm. Thepurpose of the participation and involvement of managers in the information technologysystems are for provide quality services to the public (users), so that users can feel satisfied andpricise in taking decisions.Keyword: Participation of manager, involvement of managers, quality dimention, userssatisfication, and taking decision